مبدأ الشفافية لمكافحة الفساد الإداري في البلديـــــة - بوخممة, شوقي (University of Eloued جامعة الوادي, 2022)
تمحورت د ا رستنا حوؿ تكريس مبدأ الشفافية الإدارية لمكافحة الفساد الإداري في البمديات الج ا زئرية، ففي الشؽ النظري منيا تناولنا الإطار المفاىيمي لظاىرة الفساد: مفيوميا، أسبابيا، صورىا. كما عرّجنا عمى مبدأ الشفافية الإدارية مف حيث مفي وميا وعناصرىا مف علبنية المعمومات وتسبيب الق ا ر ا رت والرد عمى ع ا رئض المواطنيف. أما في الجانب التطبيقي، فمقد قمنا بإسقاط ما ت عرضو في الجزء النظري عمى الجزء التطبيقي، مف خلبؿ التطرؽ إلى أبرز الج ا رئ التي نخرت البمديات الج ا زئرية كالرشوة، سوء استغلبؿ الوظيفة، الإختلبس... ث استعرضنا آلية التصدي ليا بواسطة تجسيد الشفافية الإدارية، مف خلبؿ علبنية المعمومات في مداولات البمدية، التوظيؼ، الصفقات العمومية اولإنتخابات المحمية ون ا زىتيا ومحاربة أشكاؿ الجريمة الإنتخابية.Our study focused on the principle of administrative transparency to combat administrative corruption in Algerian municipalities, in the theoretical part of which we dealt with the conceptual framework of the phenomenon of corruption: its concept, its causes, its forms. We also referred to the principle of administrative transparency in terms of its concept and elements of the openness of information, the reason for decisions and the response to citizens ' petitions. On the practical side, we have dropped what was presented in the theoretical part on the practical part, by addressing the most prominent crimes that gnawed Algerian municipalities such as bribery, abuse of job, embezzlement... Then we reviewed the mechanism to address it by embodying administrative transparency, through the openness of information in municipal deliberations, employment of public transactions, local elections, their integrity and the fight against forms of electoral crime
مدكرة ماستر
Keywords: الفساد الإداري، الشفافية، ج ا رئ الفساد، البمدية، المنتخبوف; administrative corruption, transparency, corruption crimes, municipality, elected